The paradox of disengagement: Bodily displays of inattention in couple therapy - Peräkylä, Anssi; Taurogiński, Bartłomiej; Dejko-Wańczyk, Karolina; Józefik, Barbara; Furgał, Mariusz; Matusiak, Feliks; Janusz, Bernadetta (Frontiers in Communication, 2023)
Using concepts coming from Goffman and theory of intercorporeality, the paper describes the non-speaking spouses’ responses to the complaints made about them by the other spouse, in the context of couple therapy first consultations. While the turn-taking system of couple therapy effectively precludes the possibility of a direct verbal response, the non-speaking spouses often display bodily their disengagement from their spouse’s talk. Using multimodal conversation analysis as method, we show the repertoire of such disengagement behaviors and trace the moment-by-moment contexts where they arise. While the disengagement behaviors embody their producer's inattention to the spouses talk, they in the same time, paradoxically, are interactional moves produced in the presence of others, conveying their producer's negative relation to the ongoing talk. We argue that the the timing of the practices of disengagement involves anticipation of the direction of talk: the non-speaking spouses display disengagement in moments when the speaking spouse’s talk takes a direction towards an intensification of complaint about them.